Analisis Mitigasi Bencana Banjir Akibat Sedimentasi dalam Perubahan Tata Guna Lahan Kawasan Permukiman Sepadan Kali Acai pada Tahun 2014 – 2024 - Asmul Wawan Kirana; Elisabeth V Wambrauw; Julian Wairata (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Flooding is a hydrometeorological disaster that frequently occurs in Jayapura City, especially in the catchment areas along the Acai River Basin. One of the main factors causing flooding is increased sedimentation triggered by massive land-use changes. This study aims to analyze the relationship between land conversion, increased sedimentation, and flooding in the catchment areas belonging to the Acai River during the period 2014–2024. The method used is a mixed-method approach that combines quantitative, qualitative, and spatial analysis. Data were collected through satellite image interpretation, field surveys, sedimentation measurements, and interviews with the community and related agencies. Spatial analysis was conducted to identify the dynamics of land-use changes and sedimentation zoning. Meanwhile, hydrological analysis was conducted using the Mononobe method and rational calculations to calculate the maximum flood discharge based on annual rainfall and runoff coefficient. The results of the study indicate that over the past decade there has been an increase in built-up land area of ​​more than 80%, which has resulted in an increase in runoff coefficients from 0.223 in 2014 to 0.370 in 2024. The maximum flood discharge has also increased significantly from 60.56 m³/s to 100.41 m³/s. Furthermore, river sedimentation has also increased drastically, especially in the middle and downstream parts of the watershed. The correlation map shows that areas experiencing significant land use conversion are also locations with high sedimentation levels and recurrent flooding. These findings indicate a strong link between land use conversion and increased flood risk through sedimentation mechanisms that provide river channel capacity. Therefore, an integrated watershed management strategy is needed, including controlling land use conversion and restoring riverbank vegetation to minimize the impact of future flooding.